Measurements of the charm jet cross section and nuclear modification factor in pPb collisions at root sNN=5.02TeV - Sirunyan,AM; Tumasyan,A; Adam,W; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Eroe,J; Flechl,M; Friedl,M; Fruehwirth,R; et al. (PHYSICS LETTERS B, 2017)
The CMS Collaboration presents the first measurement of the differential cross section of jets from charm quarks produced in proton–lead (pPb) collisions at a nucleon–nucleon center-of-mass energy of sNN=5.02TeV, as well as results from charm quark jets in proton–proton (pp) collisions at s=2.76 and 5.02TeV. By comparing the yields of the pPb and pp collision systems at the same energy, a nuclear modification factor for charm jets from 55 to 400GeV/c in pPb collisions at sNN=5.02TeV of RpA=0.92±0.07(stat)±0.11(syst) is obtained. This is consistent with an absence of final-state energy loss for charm quarks in pPb collisions. In addition, the fraction of jets coming from charm quarks is found to be consistent with that predicted by pythia 6 for pp collisions at s=2.76 and 5.02TeV, and is independent of the jet transverse momentum from 55 to 400GeV/c.